Resolving Rapid Radiation of Voles and Lemmings (Arvicolinae: Cricetinae, Rodentia) with QuaddRAD Sequencing and Transcriptome Analysis - Natalia Abramson; Elizaveta Skalon; Olga Bondareva; Semen Bodrov; Tatyana Petrova; Ivan Dvoyashov (Diversity)
Voles and lemmings (subfamily Arvicolinae) remain some of the most difficult groups for disentangling phylogenetic relations owing to recent and very fast explosive radiation. The rapid radiation events are challenging for phylogenetic analysis and produce bushes of various shapes that are impossible to resolve with a straightforward approach using individual loci. Here using the quaddRAD-seq technique and transcriptomes, we tested whether data from the nuclear genome are consistent with trees inferred earlier from individual loci and from mitogenomes in topology and divergence dating. Both the transcriptome and quaddRAD-seq data convincingly place Arvicola as the earliest derivative within Arvicolini. This result is in agreement with the fossil record and conventional taxonomy. For the first time, whole-genome sequencing data resolved relations within the third radiation wave of the subfamily’s taxa, namely the tribes Arvicolini, Lagurini, and Ellobiusini, which have formed polytomy in mitochondrial trees in earlier articles. This study indicates that divergence dating is highly dependent on the number and position of calibration points in a tree and on taxa sampling. In terms of phylogenetic inference, the position of nodes with insufficient taxa representation is the most susceptible to errors.